IMAGE, BRAND AND THE SACRED (INDIA) - Kumar, Sudhir (International Journal of Research -GRANTHAALAYAH, 2015)
In the age of global digital revolution the ways of seeing things, the concept of visuality, frequency of images, their interplay and the multiplicity of their meaning have tended to become the culture of the day. Proliferation of screen culture, plethora of print images and the abundance of commercial visuals all around have caused an unprecedented changes in the methods of consuming images within the cultures. In India, where it is difficult to imagine a culture without images and visuals, ‘seeing’ consists more than what is commonly considered mere as ocular sight. ‘Seeing’ cannot be without ethics in India and images here always need a positive symbolism, and a sense of sacredness is always attached to the most of them. Branding in an age of visual proliferation has more to depend on the dynamics of images and the visual symbols which situate themselves at the liminal zones between consumers’ own real world and the virtual worlds of the brands projected by corporate sectors. This paper taking ethico-spiritual stance attempts at rethinking on the present approaches of branding in Indian context where consideration for dominant and diverse visual cultures appear to be pertinent.